Cardiac hydatidosis : A rare infection of the heart with hydatid cyst of Echinococcus granulosus can produced anaemia - Khalaf, Amal Kh. (University of Thi-Qar Journal of Science, 2014)
Rarely , heart was infected with hydatid cyst of E. granulosus , where the current study were recorded only one infection of heart with hydatid cyst among 225 male of mice experimentally infected with hydatid cyst leading to produced anaemia. Histological examination of hydatid cyst components was explained presence of three layers include fibrous layer, laminated layer, and germinal layer or endocyst. So there is a granulomatous fibrous tissue in the pericardium.